Study of sorption and desorption of Cd (II) from aqueous solution using isolated green algae Chlorella vulgaris - Mahendra Kumar; Alak Kumar Singh; Mohd. Sikandar (Applied Water Science, 2018)
Abstract In the present investigation, isolated green algae Chlorella vulgaris has been proven to be a very effective and promising adsorbing biomaterial for Cd (II) removal from aqueous solution in batch experiments. Adsorption features of algae were studied as function of time, pH, initial Cd (II) concentration and algal biomass dosages. Kinetics and adsorption equilibrium isotherms of algal biomass were obtained for batch experiments. Kinetic data were best fitted to the pseudo-second-order where adsorption capacity (q e) values agree to experimental values. Langmuir isotherm model which shows the existence of monolayer adsorption under the experimental conditions best fitted to the obtained equilibrium data. The maximum adsorption capacity calculated by Langmuir model was 97.43 mg/g. FTIR, SEM, metal mapping were performed for virgin algal biomass and biomass loaded with Cd (II) to analyze the mechanism of adsorption. The various parameters of thermodynamics viz, ΔH, ΔG and ΔS, show endothermic, feasible and spontaneous behaviour, respectively, in sorption process. Desorption experiments were carried out insight of various parameters which resulted 0.1 M EDTA had commanding recovery of Cadmium metal ions. Recyclability study of algal biomass indicates promising future as it remains unaffected after five cycles with very less adsorption capacity loss (5.8%).